Optimizing of Synthesis of High Purity HMX Using Polyphosphoric Acid by Response Surface Method - M.A. Zarei; D. Fallah; M. M. Bahri rasht Abadi; M. Mahyari; F. Khori Amirabadi; M. Piryaee (Iranian Journal of Chemical Engineering)
1,3,5,7-tetranitro-1,3,5,7-tetraazacyclooctane (HMX) is one of the most powerful explosives of which the purity may have a significant effect on increasing the performance of rocket engines. In this research, the synthesis of high purity HMX is presented using the nitration of 1,5-diacetyl-3,7-dinitrooctahydro-1,3,5,7-tetrazocine (DADN) with a mixture of nitric acid and polyphosphoric acid. The nitration parameters including temperature, time, and the concentration of nitric acid, and polyphosphoric acid were optimized for the desirable purity and efficiency using the response surface method and central composite method (CCD). Based on the optimization, HMX was obtained with a purity of 99% and an efficiency of 92.9% at a temperature of 70°C and the time duration of 70 minutes with a molar ratio of polyphosphoric acid to nitric acid of 1:1:6.